2017
DOI: 10.1002/1873-3468.12724
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans WRN helicase promotes double‐strand DNA break repair by mediating end resection and checkpoint activation

Abstract: The protein associated with Werner syndrome (WRN), is involved in DNA repair, checkpoint activation, and telomere maintenance. To better understand the involvement of WRN in double-strand DNA break (DSB) repair, we analyzed the combinatorial role of WRN-1, the Caenorhabditis elegans WRN helicase, in conjunction with EXO-1 and DNA-2 nucleases. We found that WRN-1 cooperates with DNA-2 to resect DSB ends in a pathway acting in parallel to EXO-1. The wrn-1 mutants show an aberrant accumulation of replication prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Indeed, we found that depletion of WRN helicase abrogated the short oligonucleotides generated by Dna2 (Supplementary Figure S5E, S5F), consistent with the previous finding that Dna2 acts in conjunction with WRN (or BLM) in resection (55,63,98,106). Interestingly, depletion of WRN from the extract also dramatically inhibited the generation of long cleavage products in the presence or in the absence of Dna2 (Supplementary Figure S5E and F), suggesting that WRN is also involved in the CtIP–MRN pathway of resection initiation.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, we found that depletion of WRN helicase abrogated the short oligonucleotides generated by Dna2 (Supplementary Figure S5E, S5F), consistent with the previous finding that Dna2 acts in conjunction with WRN (or BLM) in resection (55,63,98,106). Interestingly, depletion of WRN from the extract also dramatically inhibited the generation of long cleavage products in the presence or in the absence of Dna2 (Supplementary Figure S5E and F), suggesting that WRN is also involved in the CtIP–MRN pathway of resection initiation.…”
Section: Discussionsupporting
confidence: 91%
“…We started with a C. elegans model of WS, wrn-1(gk99) , which has a 196-bp deletion mutation resulting in the complete absence of the WRN-1 protein 26,27 . This strain recapitulates major features of WS patients, including impaired DSBR, progeroid tissue phenotypes, and shorter lifespan 3,27,28 . Similar to the observations in human WS cells, we found reduced mitochondrial network complexity (42% reduction, Fig.…”
Section: Resultsmentioning
confidence: 80%
“…We identified 20 copies of G2E3 in the YHSC genome, compared with three at most in all other genomes examined ( Figure 4 E). WRN , a member of the RecQ family, is a checkpoint protein in the replication fork recovery and double-strand DNA break repair pathway with ATP-dependent 3′-5′ DNA helicase activity 72 , 77 , 93 ( Figures 4 A and 4C). Far more copies of WRN were identified in the YHSC genome than in any other genome examined ( Figure 4 F).…”
Section: Resultsmentioning
confidence: 99%
“…(A) In the fork recovery pathway, the ssDNA-RPA complex recruits some proteins. 72 , 77 Meanwhile, BRCA2 catalyzes the formation and stabilization of RAD51-ssDNA filaments, which protects nascent DNA from MRE11-mediated nucleolytic degradation. 69 , 78 Then, CHK1 is activated with the help of G2E3, 79 and the replication fork restarts after obstacle removal.…”
Section: Resultsmentioning
confidence: 99%